2022
DOI: 10.3389/fceng.2021.794194
|View full text |Cite
|
Sign up to set email alerts
|

Spatially Resolved Operando Synchrotron-Based X-Ray Diffraction Measurements of Ni-Rich Cathodes for Li-Ion Batteries

Abstract: Understanding the performance of commercially relevant cathode materials for lithium-ion (Li-ion) batteries is vital to realize the potential of high-capacity materials for automotive applications. Of particular interest is the spatial variation of crystallographic behavior across (what can be) highly inhomogeneous electrodes. In this work, a high-resolution X-ray diffraction technique was used to obtain operando transmission measurements of Li-ion pouch cells to measure the spatial variances in the cell durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 27 publications
1
9
0
Order By: Relevance
“…It is known that thermal inhomogeneities in cells can create a variation in local cell impedance and current density 64,65 and in turn cause differences in the SoC across a cell. 66 Higher current densities at the tabs of pouch cells have also been experimentally confirmed 67 and in an in-situ synchrotron X-ray diffraction experiment on a pouch cell the area under the positive tab was found to be of a higher SoC compared to the rest of the cell 5 . In a separate HELM study on a singlephase NMC622 pouch cell, Yu et al found that the edges and corners were of a lower SoC than the middle of cell.…”
Section: Discussionmentioning
confidence: 75%
See 3 more Smart Citations
“…It is known that thermal inhomogeneities in cells can create a variation in local cell impedance and current density 64,65 and in turn cause differences in the SoC across a cell. 66 Higher current densities at the tabs of pouch cells have also been experimentally confirmed 67 and in an in-situ synchrotron X-ray diffraction experiment on a pouch cell the area under the positive tab was found to be of a higher SoC compared to the rest of the cell 5 . In a separate HELM study on a singlephase NMC622 pouch cell, Yu et al found that the edges and corners were of a lower SoC than the middle of cell.…”
Section: Discussionmentioning
confidence: 75%
“…Misalignment is a problem because it causes a reduction in surface area overlap between the electrode layers, meaning that lithium is left inactive during cycling and in turn causes capacity loss. 5 More importantly, Figures 5b-e show that gas formation related to electrolyte depletion was observed in both R2 and F3 samples after ageing. X-ray imaging and subsequent quantification of liquid electrolyte in this region allow for comparison of electrolyte 'depletion' that can result from different displacements.…”
Section: X-ray Ct Measurementsmentioning
confidence: 88%
See 2 more Smart Citations
“…Nowadays, lithium-ion batteries (LIBs) are the important power sources for portable electronics, electric vehicles, aerospace, and deep-sea diving devices due to their high energy density, acceptable cycle life, and no memory effect (Wang et al, 2020;He et al, 2021). With the continuous expansion of the application fields of LIBs, lots of efforts have been made to further improve their energy density and safety (Leach et al, 2022;Li et al, 2022;Yang et al, 2022). So far, Nickel-rich LiNi x Co y Mn 1-x-y O 2 (NCM for short, x ≥ 0.6) materials, specially, Nickel-rich LiNi 0.8 Co 0.1 Mn 0.1 O 2 (NCM811 for short) positive electrodes are one of the most promising positive electrodes for utilization in the next-generation of lithium-ion batteries (Li et al, 2020;Xue et al, 2021).…”
Section: Introductionmentioning
confidence: 99%